The European Mind-set, European Opinion and Economic Developments in 2007-2017: Major Changes of Public Opinion and the European Mind-set in Years 2004-2018 - Jari Kaivo-oja; Theresa Lauraéus (Kaunas University of Technology, 2022)
Abstract
This study reports major changes in public opinion in the European Union. First part of the study includes (1) citizens´ assessments of the most important issues facing the EU at the moment, (2)
The second part of study report changes in (1) national economic situation evaluations, (2) European economic situation evaluations, (3) European economic crisis recovery evaluations (the impact on the crisis on jobs), (4) evaluations of Euro-optimism vs. pessimism, (5) evaluations about the support for the Euro area and (6) evaluations support for the euro.  All these changes of the Standard Eurobarometer results are mirrored in relation to long-run GDP changes of the European Union (EU-28).
Third part of the study analyses the four key elements of European mind-sets. In general decision theory and general systems theory, a mind-set is a set of assumptions, beliefs, methods, or notations held by one or more people or groups of people. In the field of future studies the concept and the analysis of mind-set have been discussed in many global studies. From this perspective it is interesting to elaborate the European mind-set and its status. The study is based on the very latest “Future of Europe” datasets (September 2017). From these three perspectives this study is relevant for European integration studies.